Going lean : how the best companies apply lean manufacturing principles to shatter uncertainty, drive innovation, and maximize profits - Ruffa, Stephen A., 1961- (AMACOM/American Management Association, 2008)
Follow the lead of Toyota, Southwest Airlines, and Wal-Mart and embrace ""Lean Dynamics"" for business success
Keywords: Business logistics.; Production management.; Manufacturing processes.; Organizational change.; Lean manufacturing.; elektronické knihy; electronic books